USING PROJECT TECHNOLOGIES IN TEACHING SUBJECT-ORIENTED PROGRAMMING LANGUAGES (American Journal of Interdisciplinary Research and Development, 2022)
This article is devoted to the methodology of using design technologies in teaching modern programming languages in higher educational institutions. Based on reliable sources, it reveals the advantages of using design technologies in teaching students about domain-specific programming languages, their specific features and methods of application. Theoretical information is enriched with concrete examples. Appropriate recommendations have been developed on the problem under consideration.